2018
DOI: 10.3389/fphys.2018.01006
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Exercise-Induced Activation of Antioxidant Enzymes in the Blood of Women and Men

Abstract: Objective: Physical exercise changes redox balance in the blood. The study aim is to determine gender-related differences in enzymatic antioxidant defense [superoxide dismutase, catalase (CAT), and glutathione peroxidase (GPx)] during the initial period following anaerobic exercise and 24 h after its completion.Methods: Young, non-training participants (10 women and 10 men) performed a single anaerobic exercise, which was a 20-s maximal cycling sprint test. Blood was collected before and after completing the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 42 publications
2
35
3
Order By: Relevance
“…ere are several reports that showed SOD level does not change following exercise [73,74]. Wiecek and colleagues in 2018 reported that blood SOD level showed similar changes following anaerobic exercise in women and men [75]. In contrast to our result, it has been reported that SOD level was significantly higher in female than in male before and after exercise [76].…”
Section: Discussioncontrasting
confidence: 97%
“…ere are several reports that showed SOD level does not change following exercise [73,74]. Wiecek and colleagues in 2018 reported that blood SOD level showed similar changes following anaerobic exercise in women and men [75]. In contrast to our result, it has been reported that SOD level was significantly higher in female than in male before and after exercise [76].…”
Section: Discussioncontrasting
confidence: 97%
“…Short, dynamic anaerobic exercise, such as a 20-s bicycle sprint, induces enormous multidirectional biochemical changes, including metabolic, hormonal, and immunological ones. It has been shown that, both single anaerobic exercises (Wiecek et al, 2015, 2017, 2018), as well as a series of anaerobic exercises (Bogdanis et al, 2013), induce oxidative stress immediately after the exercise and also during the early period of recovery, and even 24 h after its completing. The effect of anaerobic exercise is also a significant increase in the concentration of IL-6 and the number of neutrophils and monocytes, the number of which was also increased 24 h after completion of the effort (Meyer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, no subjects were receiving any drugs, antioxidants, or anabolic-steroid supplements at the time of the study. All subjects had normal biphasic menstrual cycles (9). The study took place in the offseason of competitions.…”
Section: Participantsmentioning
confidence: 99%
“…Moreover, eccentric exercise induces a significant increase in the plasma TAC and MDA levels in sedentary women (8). In contrast, one study showed that 20-s maximal cycling sprint anaerobic exercise evoked a significant reduction in SOD, GPx, and CAT activity 15 min after exercise in nontrained participants (9). Other studies have not shown any significant changes in MDA levels and antioxidant enzyme activities in sera and lymphocytes after acute swimming (10), prolong cycling exercise (11), and graded exercise test (12) in trained athletes.…”
Section: Introductionmentioning
confidence: 96%